Polymeric Micellar Co‐delivery of Resveratrol and Curcumin to Mitigate In Vitro Doxorubicin‐Induced Cardiotoxicity. Issue 8 (9th June 2014) - Carlson, Lisa Janssen; Cote, Brianna; Alani, Adam WG; Rao, Deepa A.
<x xml:space="preserve">Abstract</x> Resveratrol (RES) and curcumin (CUR) have free radical scavenging ability and potential chemosensitizing effects. Doxorubicin hydrochloride (DH) is a potent chemotherapeutic with severe cardiotoxicity. We hypothesize that RES and CUR co‐loaded in Pluronic® micelles and co‐administered with DH will result in cardioprotective effects while maintaining/improving DH anti‐proliferative effect in vitro. RES–CUR at a molar ratio of 5:1 in F127 micelles (mRC) were prepared and characterized for size, drug loading, and release. In vitro cell viability and apoptosis assays in ovarian cancer cells (SKOV‐3) and cardiomyocytes (H9C2) with either individual drugs or RES–CUR or mRC in combination with DH were conducted. Combination index (CI) analysis was performed to determine combination effects. Reactive oxygen species (ROS) were quantified in H9C2 for DH, and combinations. The mRC solubilized 2.96 and 0.97 mg/mL of RES and CUR, respectively. Cell viability and CI studies indicated that the combinations were synergistic in SKOV‐3 and antagonistic in H9C2 cells. Caspase 3/7 activity in combination treatments was lower than with DH alone in both cell lines. ROS activity was restored to baseline in H9C2 cells in the micelle combination groups. Co‐administration of mRC with DH in vitro mitigates DH‐induced cardiotoxicity through reduction in apoptosis and ROS while improving DH potency in ovarian cancer cells. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2315–2322, 2014